Pre-Pregnancy Diet and Vaginal Environment in Caucasian Pregnant Women: An Exploratory Study - Dall’Asta, Margherita; Laghi, Luca; Morselli, Sara; Re, Maria Carla; Zagonari, Sara; Patuelli, Giulia; Foschi, Claudio; Pedna, Maria Federica; Sambri, Vittorio; Marangoni, Antonella; Danesi, Francesca (Frontiers in Molecular Biosciences, 2021)
Vaginal microbes and their metabolic products have crucial functions, affecting local immunity development and maternal-fetal health. The composition of the vaginal microbiome can vary in response to various factors, including body mass index (BMI), and diet. In this study we get new insights into the vaginal ecosystem of Caucasian women (n=24) at the first trimester of pregnancy, assessing whether pre-pregnancy diet can affect the structure of the vaginal environment in terms of bacterial composition and vaginal metabolite concentration. We characterized (i) the vaginal bacterial composition (Nugent score), (ii) the vaginal metabolic profiles (1H-NMR spectroscopy) and (iii) the dietary nutrient intake by means of a validated food frequency questionnaire. Pre-pregnancy BMI was negatively related to vaginal health status, indicating that women who begin pregnancy overweight/obese have a greater occurrence of vaginal dysbiosis during pregnancy. A lactobacilli-dominated vaginal microbiota was negatively associated with higher pre-pregnancy intake of animal-sourced protein. Conversely, a higher pre-pregnancy consumption of total carbohydrates and sugars seemed to be a protective factor for vaginal health. The vaginal environment of BV-women was characterized by higher levels of biogenic amines and organic acids, whereas higher levels of phenylpropionate and diverse amino acids were fingerprints of a healthy vaginal status. A significant association between a higher pre-pregnancy BMI and several dysbiosis-related vaginal metabolites was also found. Our study shed light on the role of pre-pregnancy BMI and diet on the vaginal environment during pregnancy, underlining the importance of limiting protein intake from animal foods to maintain a healthy lactobacilli-dominated microbiota.